Penguatan Kapasitas Bagi Mahasiswa Program Mata Kuliah Antropologi Kehutanan untuk Mensosialisasikan (HAM) Hak Asasi Manusia Bidang Kehutanan dan Lingkungan - Laxmi; Sarlan Adi Jaya; Harnina Ridwan; Abdul Alim; Aslim (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
This community service activity aims to find out how human rights institutions play a role in maintaining and protecting community rights, especially in the context of forestry. The background of this activity stems from the fact that PUSPA HAM, as an institution that focuses on human rights issues in Southeast Sulawesi, is an appropriate destination to understand how forestry and human rights issues are interrelated. This activity involved observation, interviews, discussions, questions and answers and lectures as well as assistance from the PKM team. The results showed that PUSPA HAM has several activities that are effective in addressing human rights issues in Southeast Sulawesi. These activities include human rights education for the community, advocacy for human rights violations, monitoring and evaluation of human rights implementation in Southeast Sulawesi. In carrying out its activities, PUSPA HAM Southeast Sulawesi has shown a strong commitment to fighting for the rights of indigenous peoples and local communities. It has become one of the leading human rights organizations in Southeast Sulawesi. This activity involves collaboration between universities, non-governmental organizations (NGOs), and government agencies, including PUSPA HAM (Center for Strengthening and Protecting the Rights of Indigenous and Local Communities), WALHI, and the Forestry Service. This collaboration aims to increase awareness and understanding of human rights in Southeast Sulawesi. PUSPA HAM faces challenges in gaining support from the government. The government has policies that do not support human rights in Southeast Sulawesi. In the face of these challenges PUSPA HAM has shown a strong commitment to fighting for the rights of indigenous peoples and local communities.